2006
DOI: 10.1002/pca.939
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and quantification of gymnemic acids through gymnemagenin from callus cultures ofGymnema sylvestre

Abstract: The phyto-constituents of Gymnema sylvestre are used in the treatment of diabetes and obesity. The present work reports on the extraction of gymnemic acid through gymnemagenin from callus cultures of G. sylvestre. Components were separated on pre-coated silica gel 60 GF254 plates with chloroform:methanol (8:2) and scanned using a densitometric scanner at 205 nm in the near-UV region. Linearity of determination of gymnemagenin was observed in the range 2-10 microg. The average percentage recovery of gymnemageni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…UV spectrophotometer peak area data were compared with standard gymnemic acid (Table III). Gymnemagenin and GA were significantly increased in callus culture through leaf explants of G. sylvestre [10][11][12][13][14][15][16]. In the present study, maximum GA production was observed in MS medium supplemented with OPGRs under blue light induced 4.4 fold as compared with white fluorescent light and out of which 2.8 fold was found in intact leaves determined by HPLC analysis.…”
Section: Hplc Studies In Leaf and Callus Extractsmentioning
confidence: 49%
See 1 more Smart Citation
“…UV spectrophotometer peak area data were compared with standard gymnemic acid (Table III). Gymnemagenin and GA were significantly increased in callus culture through leaf explants of G. sylvestre [10][11][12][13][14][15][16]. In the present study, maximum GA production was observed in MS medium supplemented with OPGRs under blue light induced 4.4 fold as compared with white fluorescent light and out of which 2.8 fold was found in intact leaves determined by HPLC analysis.…”
Section: Hplc Studies In Leaf and Callus Extractsmentioning
confidence: 49%
“…Gymnemic acid (GA), mixture triterpene saponins, was discovered in 1847 to temporarily reduce the sweet taste of sugar in humans [9]. In vitro developed callus trends to produce various bioactive compounds, including GA and gymnemagenin [10]. However, external factors like phytohormone, shaking speeds, pH and medium play important roles in GA production in suspension cultures [11].…”
Section: Introductionmentioning
confidence: 99%
“…Gymnemic acid and GG are believed to be the major active compounds of G. sylvestre, and GG, which enters the circulation after hydrolysis of gymnemic acids, is a common genin for most of the gymnemic acids [4][5][6]. It has been a clinical concern that herbal products containing a number of natural compounds can cause pharmacokinetic interactions with modern medicines, particularly in combination.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Gymnema's antidiabetic activity appears to be due to a combination of mechanisms. It increases the activity of enzymes responsible for glucose uptake and utilization, and inhibits peripheral utilization of glucose by somatotrophin and corticotrophin [180]. Plant extracts have also been found to inhibit epinephrine-induced and corticosteroid-induced hyperglycemia [102].…”
Section: Plants Possessing Hypoglycemic Activitymentioning
confidence: 99%